Morfoanalitica Therapy as a therapeutic resource post breast cancer surgery for women - Pachioni, Fernanda Stellutti Magrini; Palma, Mariana Romanholi; Mantovani, Alessandra Madia; Fregonesi, Cristina Elena Prado Teles (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Women with breast cancer may present, in addition to physical limitations, changes in emotional aspects. In physical therapy, it is unusual to consider the mind-body dialogue, even when it comes to diseases with great impact on bio-psychosocial aspects, such as breast cancer. However, therapies are emerging with a psychosomatic nature, such as morphonalitic therapy, which includes bodily, sensory, emotional and verbal aspects. Objective: To verify the effects of morphonalitic therapy on the treatment of anxiety, depression and self-esteem in women after breast cancer. Furthermore, it presents some verbal reports of sessions in order to include the feelings and sensations of these women and recognize, in addition to objective factors, the subjective factors that are an integral part of human stories. Method: Ten women participated in the study, undergoing 16 individual morphonalitic therapy sessions, once a week, lasting 60 minutes. They completed a scale on anxiety and depression and the Rosenberg self-esteem scale. The sessions were arranged through a structured therapeutic framework, which varied according to the therapeutic process of each participant. This included bodywork, empathetic touching contact, eye contact, stimulation of body awareness, and analysis of the patient’s body structure; during the session, the patients verbalized their feelings. Results: Depressive symptoms decreased (p = 0.0418) and self-esteem increased (p = 0.0020) after treatment. Conclusions: During the sessions, these women experienced various feelings, beyond the awakening of body awareness. It is hoped that morphonalitic therapy be applied on a larger scale as an adjunct therapy for women with breast cancer, as well as in other populations.